Numerical investigation on the mixture formation and combustion processes of a gasoline rotary engine with direct injected hydrogen enrichment. (15th August 2018) - Yang, Jinxin; Ji, Changwei; Wang, Shuofeng; Wang, Du; Ma, Zedong; Zhang, Boya
Highlights: A CFD model was established and validated for H2 -gasoline fueled rotary engine. H2 was direct injected in the combustion chamber at three injection positions. The mixtures formation and combustion processes were investigated. Proper H2 distribution burned the mixtures in the rear region of chamber. Abstract: The present study established a computational fluid dynamics model and numerically investigated the mixture formation and combustion processes of a gasoline rotary engine enriched by the direct injected hydrogen at three injection positions. It is found that the special flow field inside rotary engine combustion chamber has strong interactions with the hydrogen jet-flow, and the hydrogen distribution could further influence the charge combustion. At the end stage of compression stroke, the mainstream field whose direction same to rotor movement is formed, and a vortex with high vorticity existed in the front of combustion chamber. With the influences of mainstream field and vortex, the hydrogen almost fills half of combustion chamber and properly rich hydrogen region distribution is obtained near the spark plug with the injection position close to the spark plug. In addition, proper equivalence ratio distribution could enhance the flame propagation and mixtures combustion completeness in rear region of combustion chamber. Compared with injection position far away from the spark plug, the peak in-cylinder pressure of the injection position close to the spark plug increases by 18.3%, and carbon monoxide emission is decreased obviously, but nitrogen monoxide emission increases due to higher in-cylinder temperature.